A Fully Coupled CFD-DMB Approach on the Ship Hydroelasticity of a Containership in Extreme Wave Conditions - Yujia Wei; Atilla Incecik; Tahsin Tezdogan (Journal of Marine Science and Engineering, 2022)
In this paper, we present a fully coupled computational fluid dynamic (CFD) and discrete module beam (DMB) method for the numerical prediction of nonlinear hydroelastic responses of a ship advancing in regular and focused wave conditions. A two-way data communication scheme is applied between two solvers, whereby the external fluid pressure exported from the CFD simulation is used to derive the structural responses in the DMB solver, and the structural deformations are fed back into the CFD solver to deform the mesh. We first conduct a series of verification and validation studies by using the present CFD–DMB method to investigate the global ship motion, vertical bending moments (VBMs), and green water phenomenon of the ship in different regular wave conditions. The numerical results agreed favourably with the CFD–FEA model and experimental measurements. Then, the extreme ship motions are studied in focused wave conditions to represent extreme sea conditions that a ship may experience in a real sea state. According to the conclusion drawn from the numerical simulations, it is founded that the focused wave case will lead to the increase of the longitudinal responses of the hull compared to regular wave condition, i.e., the heave, pitch, and total VBMs rise about 25%, 20% and 9%, respectively. In focused wave conditions, intensive ship responses and severe waves cause stronger slamming phenomena. It is found that the instantaneous impact pressure from the focused wave is higher and sharper compared to the regular waves and comes along with the obvious green-water-on-deck phenomena.